The Variation of Propagation Velocity According to Substrate Material of Band Pass Filter - Lee, Dong-Yoon; ., . (International Journal of Engineering and Technology, 2018)
Background/Objectives: The SAW filter has a frequency characteristic determined by the geometry of the IDT electrode, and is widely used as a band-pass filter for passing only a signal having a specific frequency.Methods/Statistical analysis: The features of this filter are high stability and reliability and enable mass production using semiconductor processes.Findings: The MCB process lift off method was used to fabricate the filter to solve the difficulties of the SAW filter process. In particular, we fabricated ZnO thin films with excellent c-axis preferential orientation, high resistivity of more than 106Î©cm, and flat surfaces, and fabricated SAW filters using ZnO thin films as deposition conditions suitable for application to SAW filters. ZnO thin films deposited under conditions of RF power of 150W, chamber pressure of 10mTorr, substrate temperature of 200 Â° C and gas mixture ratio of Ar/O2 of 50/50 as sputtering gas have excellent c-axis preferential orientation, high specific resistance and flat surface shape. Then, ZnO piezoelectric thin film was deposited on SiO2 substrate by RF magnetron sputtering method and the SAW filter was fabricated by the MCB lift off method to analyze the frequency characteristics. And compared with the SAW filter fabricated on the LiNbO3 substrate, which is a piezoelectric substrate.Improvements/Applications: The propagation speed of the SAW filter using the ZnO thin film was determined by the variation of the center frequency due to the deposition of the ZnO thin film.Â Â